RITPBC: B-cell depleting therapy (rituximab) as a treatment for fatigue in primary biliary cirrhosis: study protocol for a randomised controlled trial. Issue 8 (20th August 2015) - Jopson, Laura; Newton, Julia L; Palmer, Jeremy; Floudas, Achilleas; Isaacs, John; Qian, Jessica; Wilkinson, Jennifer; Trenell, Mike; Blamire, Andrew; Howel, Denise; Jones, David E
Abstract : Introduction: Primary biliary cirrhosis (PBC) is an autoimmune liver disease with approximately 50% of patients experiencing fatigue. This can be a particularly debilitating symptom, affecting quality of life and resulting in social isolation. Fatigue is highlighted by patients as a priority for research and patient support groups were involved in designing this trial. This is the first randomised controlled trial to investigate a treatment for fatigue in PBC. The trial protocol is innovative as it utilises novel magnetic resonance spectroscopy (MRS) techniques as an outcome measure. The protocol will be valuable to research groups planning clinical trials targeting fatigue in PBC and also transferrable to other conditions associated with fatigue. Methods and analysis: RITPBC is a Medical Research Council (MRC) and National Institute for Health Research (NIHR) Efficacy and Mechanism Evaluation Programme (EME)-funded project. It is a phase II, single-centre, randomised controlled, double-blinded trial comparing rituximab with placebo in fatigued PBC patients. 78 patients with PBC and moderate to severe fatigue will be randomised to receive two infusions of rituximab or placebo. The study aims to assess whether rituximab improves fatigue in patients with PBC, the safety, and tolerability of rituximab in PBC and the sustainability of any beneficial actions. The primary outcome will be an improvement in fatigue domain score of the PBC-40, a disease-specific quality of life measure, evaluated at 12-week assessment. Secondary outcome measures include novel MRS techniques assessing muscle bioenergetic function, physical activity, anaerobic threshold and symptom, and quality of life measures. The trial started recruiting in October 2012 and recruitment is ongoing. Ethics and dissemination: The trial has ethical approval from the NRES Committee North East, has Clinical Trial Authorisation from MHRA and local R&D approval. Trial results will be communicated to participants, presented at national and international meetings and published in peer-reviewed journals. Trial registration number: ISRCTN03978701.